Endoscopic Resection of Gastrointestinal Neuroendocrine Tumors: Long-Term Outcomes and Comparison of Endoscopic Techniques - Pimentel-Nunes,Pedro (2023)
Abstract Introduction: Gastrointestinal neuroendocrine tumors (GI-NETs) are being more frequently diagnosed and treated by endoscopic resection (ER) techniques. However, comparison studies of the different ER techniques or long-term out-comes are rarely reported. Methods: This was a single-center retrospective study analyzing short and long-term outcomes after ER of gastric, duodenum, and rectal GI-NETs. Comparison between standard EMR (sEMR), EMR with a cap (EMRc), and endoscopic submucosal dissection (ESD) was made. Results: Fifty-three patients with GI-NET (25 gastric, 15 duodenal, and 13 rectal; sEMR = 21; EMRc = 19; ESD = 13) were included in the analysis. Median tumor size was 11 mm (range 4-20), significantly larger in the ESD and EMRc groups compared to the sEMR group (p < 0.05). Complete ER was possible in all cases with 68% histological complete resection (no difference between the groups). Complication rate was significantly higher in the EMRc group (EMRc 32%, ESD 8%, and EMRs 0%, p = 0.01). Local recurrence occurred in only one patient, and systemic recurrence in 6%, with size ≥ 12 mm being a risk factor for systemic recurrence (p = 0.05). Specific disease-free survival after ER was 98%. Conclusion: ER is a safe and highly effective treatment particularly for less than 12 mm luminal GI-NETs. EMRc is associated with a high complication rate and should be avoided. sEMR is an easy and safe technique that is associated with long-term curability, and it is probably the best therapeutic option for most luminal GI-NETs. ESD appears to be the best option for lesions that cannot be resected en bloc with sEMR. Multicenter, prospective randomized trials should confirm these results.